LIMIT DISTRIBUTION OF A RANK OF RANDOM SATURATED MATRIX ABOVE A FIELD GF(2) - Поперешняк, C.В. (Proceedings of National Aviation University (archive), 2012)
In this paper a theorem on the asymptotic distribution of rank of random matrices in the field GF (2) of independent random -D lines, the absence in it of unity lines and the assumption that the difference between the number of rows and number of columns of the matrix is a fixed number of random characters, .